Erosion mechanism of tabular alumina of various microstructures under different basicity of blast furnace slag. Issue 14 (15th July 2022) - Ma, Jiuhong; Zhao, Huizhong; Li, Yichong; Yu, Jun; Zhang, Han; Shi, Lida; Zhao, Yi; He, Jian
Abstract: In this study, three types of commercial tabular alumina aggregates with different microstructural characteristics were selected for corrosion tests on blast furnace slags with varying basicities. A corrosion mechanism with different microstructural characteristics is proposed, and the dominant microstructures in high- and low-basicity environments are evaluated. The pore structure was found to have a crucial influence on the dissolution of tabular alumina aggregates in the blast furnace slag. Under low-basicity (0.5–0.7) conditions, a small amount of clustered pore structure was beneficial for obtaining the maximum thickness (40–60 μm) of the isolation layer between the tabular alumina aggregate and slag. Under high-basicity (0.9–1.1) conditions, the circular pore structure tended to form a uniform and stable double-layer isolation structure of calcium hexaaluminate and MgAl2 O4 spinel.